Causes of neonatal and maternal deaths in Dhaka slums: Implications for service delivery - Khatun Fatema; Rasheed Sabrina; Moran Allisyn C; Alam Ashraful M; Shomik Mohammad; Sultana Munira; Choudhury Nuzhat; Iqbal Mohammad; Bhuiya Abbas (BMC, 2012)
Abstract Background Bangladesh has about 5.7 million people living in urban slums that are characterized by adverse living conditions, poor access to healthcare services and health outcomes. In an attempt to ensure safe maternal, neonatal and child health services in the slums BRAC started a programme, MANOSHI, in 2007. This paper reports the causes of maternal and neonatal deaths in slums and discusses the implications of those deaths for Maternal Neonatal and Child Health service delivery. Methods Slums in three areas of Dhaka city were selected purposively. Data on causes of deaths were collected during 2008-2009 using verbal autopsy form. Two trained physicians independently assigned the cause of deaths. Results A total of 260 newborn and 38 maternal deaths were identified between 2008 and 2009. The majority (75%) of neonatal deaths occurred during 0-7 days. The main causes of deaths were birth asphyxia (42%), sepsis (20%) and birth trauma (7%). Post partum hemorrhage (37%) and eclampsia (16%) were the major direct causes and hepatic failure due to viral hepatitis was the most prevalent indirect cause (11%) of maternal deaths. Conclusion Delivery at a health facility with child assessment within a day of delivery and appropriate treatment could reduce neonatal deaths. Maternal mortality is unlikely to reduce without delivering at facilities with basic Emergency Obstetric Care (EOC) and arrangements for timely referral to EOC. There is a need for a comprehensive package of services that includes control of infectious diseases during pregnancy, EOC and adequate after delivery care.